DFT studies on thiophene acetylide Ru (II) complexes for NLO purposes: tuning their electronic properties - Mendes, Paulo J. G. (2012)
Organometallic complexes have been widely used as building blocks for second-order non-linear optical (SONLO) materials, particularly 5-monocyclo-pentadienyls, as they can act as a good electron or releasing groups when bonded to highly polarisable chromophores such as thiophene based organic frameworks. Density Functional Theory (DFT) methods, especially Time Dependent methods (TD-DFT), have been successfully used for understanding the electronic factors behind the SONLO phenomenon. Recently, our studies shown that not only the 5-monocyclopentadienyliron(II) organometallic fragment plays a determinant role in order to obtain large second-order non linear optical responses but additionally electronic properties of the substituents on the thiophene moiety are also important. In this communication we present a TD-DFT study on the effect of different thiophene acetylide derivatives on the first hyperpolarizability, , in the parent 5-monocyclopentadienylruthenium(II) complexes in order to confirm the ability of these thiophene ligands as polarisable chromophores when interacting with a good electron-donor organometallic fragment such as the 5-monocyclopentadienylruthenium(II) group. We also studied the solvation effect, using the self-consistent reaction field approach (SCRF), on the electronic properties and first hyperpolarizabilities for the complex for which the higher value of static quadratic hyperpolarizability was obtained.